Strategi Adaptasi Mahasiswa Rantau dari Berbagai Negara - Alfiona Nafa Ivana Suhartono (Flourishing Journal, 2024)
Culture is something that determines how each individual behaves in living life. Most students undergo lectures in overseas areas, even willing to be far from their home areas to pursue education according to their wishes. Based on the explanation above, the author is interested in writing a symptomatic literature review that discusses the adaptation strategies of overseas students from various countries. The literature review method was carried out on ten journal articles published in the last 10 to 15 years, both from within and outside the country. In addition, some of these journal articles were obtained from three databases: Google Scholar, Springer Link, and Repository. Some of these articles discuss adaptation strategies carried out by overseas students from several regions who undergo lectures at home and abroad. The purpose of this literature review is to find out how adaptation strategies are carried out by overseas students from various countries. The results of this Systematic Literature Review are dominant students establish relationships by adjusting their culture, using the language of the majority of the destination area, looking for the same food in the destination area and often consumed by them, and the last is often contacting family. AbstrakBudaya merupakan hal yang menentukan bagaimana perilaku setiap individu dalam menjalani kehidupan. Banyak mahasiswa menjalani perkuliahan di wilayah perantauan, bahkan rela jauh dari daerah asal hanya untuk menempuh pendidikan sesuai keinginan mereka. Dari pemaparan di atas, penulis tertarik untuk menulis systhematic literature review yang membahas strategi adaptasi mahasiswa rantau dari berbagai negara. Metode literature review dilakukan terhadap10 jurnal artikel yang diterbitkan 10 sampai 15 tahun terakhir baik dari dalam maupun luar negeri. Selain itu beberapa artikel jurnal tersebut diperoleh dari tiga database yaitu Google Scholar, Springer Link, Dan Repository. Beberapa artikel tersebut membahas mengenai strategi adaptasi yang dilakukan oleh mahasiswa rantau dari beberapa daerah yang menjalani perkuliahan di dalam maupun luar negeri. Tujuan dari literature review ini adalah untuk mengetahui bagaimana strategi adaptasi yang dilakukan oleh mahasiswa perantauan dari berbagai negara. Hasil dari systhematic literatur review ini adalah mahasiswa dominan menjalin hubungan relasi dengan menyesuaikan budaya-nya, menggunakan bahasa mayoritas daerah tujuan, mencari di daerah tujuan makanan yang sama dan sering dikonsumsi oleh mereka, dan yang terakhir adalah sering menghubungi keluarga.